2018
DOI: 10.1007/s10585-018-9873-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical stress response and promotion of metastasis in colorectal cancer: a complex and heterogeneous process

Abstract: Surgery remains the curative treatment modality for colorectal cancer in all stages, including stage IV with resectable liver metastasis. There is emerging evidence that the stress response caused by surgery as well as other perioperative therapies such as anesthesia and analgesia may promote growth of pre-existing micro-metastasis or potentially initiate tumor dissemination. Therapeutically targeting the perioperative period may therefore reduce the effect that surgical treatments have in promoting metastases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 89 publications
(113 reference statements)
1
54
1
Order By: Relevance
“…Although carcinogenesis and disease progression may differ between carcinomas of different origin, basic mechanisms seem to be universal to the early metastatic process. TSE and TSF promote PMN and metastasis formation through the interplay between CTC, the immune system, stromal cells, vascular leakiness and ECM‐remodeling, all creating the perfect microenvironment for incoming tumor cells …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although carcinogenesis and disease progression may differ between carcinomas of different origin, basic mechanisms seem to be universal to the early metastatic process. TSE and TSF promote PMN and metastasis formation through the interplay between CTC, the immune system, stromal cells, vascular leakiness and ECM‐remodeling, all creating the perfect microenvironment for incoming tumor cells …”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is the mainstay in the treatment of most solid cancers. Nonetheless, emerging evidence shows that the surgical trauma, anesthesia, analgesia and postoperative complications may promote dissemination by direct effects on tumor cells, microenvironment and immune system thereby increasing the risk of recurrence …”
Section: Introductionmentioning
confidence: 99%
“…Surgical procedures that are implicated in the promotion of metastasis are addressed in reviews from Alieva et al [15] and Behrenbruch et al [16]. Using high-resolution intra-vital microscopy in a mouse glioblastoma model, Alieva et al demonstrated previously that even a minor surgical trauma, such as fine-needle biopsy, could induce tumour cell migration and proliferation that could be prevented by blocking macrophage recruitment to the site of injury through inhibition of chemokine (C-C motif) ligand 2 (CCL-2) [17].…”
Section: Surgerymentioning
confidence: 99%
“…Criticism of the LACC study is based on the lack of a standardized surgical technique including possible use of uterine manipulators and intracorporal colpotomy without vaginal cuff closure, which might represent the strongest factor for increased recurrence rates due to intraoperative tumor dissemination . We already know from different cancer entities such as colorectal or pancreatic cancer that intraoperative tumor dissemination by surgical procedures is associated with increased recurrence rates . Several authors actually promote surgical techniques for cervical cancer treatment which aim to prevent tumor spillage during surgery .…”
Section: Introductionmentioning
confidence: 99%
“…1,8,9 We already know from different cancer entities such as colorectal or pancreatic cancer that intraoperative tumor dissemination by surgical procedures is associated with increased recurrence rates. [11][12][13] Several authors actually promote surgical techniques for cervical cancer treatment which aim to prevent tumor spillage during surgery. 9,14,15 To our knowledge, studies analyzing the probability or mechanisms of intraoperative peritoneal tumor cell dissemination for cervical cancer are lacking.…”
Section: Introductionmentioning
confidence: 99%